2010
DOI: 10.1002/jnr.22493
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and classification of aggrecan‐based extracellular matrix in the thalamus of the rat

Abstract: Extracellular matrix molecules take part in functional isolation and stabilization of neuronal compartments but form a vivid interface between neuronal elements at the same time. Previous studies have shown that the accumulation of extracellular matrix, especially its typical phenotypic form, termed perineuronal nets, correlates not only with the functional properties of the single neuron but also with the functional properties of the whole brain area. In contrast to recent advances in investigating neocortex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Using double‐labeling experiments and electron microscopy, we demonstrated that matrix immunoreactive for the aggrecan core protein was indeed typical along dendritic sections and ensheathed both excitatory but mainly inhibitory synapses. This unique phenotype of extracellular matrix, i.e., the lack of perineuronal nets but the very local perisynaptic accumulation of matrix, supports the previously introduced hypothesis that perisynaptic extracellular matrix can be established by the presynaptic neuron (Brückner et al,2008; Morawski et al,2010b; Gáti et al,2010). This assumption has been made for the rat thalamus, in which neurons mostly lack perineuronal nets, but axonal coats were detected by the HAG7D4 antibody at the ultrastructural level around and in thalamic afferents (Gáti et al,2010).…”
Section: Discussionsupporting
confidence: 82%
“…Using double‐labeling experiments and electron microscopy, we demonstrated that matrix immunoreactive for the aggrecan core protein was indeed typical along dendritic sections and ensheathed both excitatory but mainly inhibitory synapses. This unique phenotype of extracellular matrix, i.e., the lack of perineuronal nets but the very local perisynaptic accumulation of matrix, supports the previously introduced hypothesis that perisynaptic extracellular matrix can be established by the presynaptic neuron (Brückner et al,2008; Morawski et al,2010b; Gáti et al,2010). This assumption has been made for the rat thalamus, in which neurons mostly lack perineuronal nets, but axonal coats were detected by the HAG7D4 antibody at the ultrastructural level around and in thalamic afferents (Gáti et al,2010).…”
Section: Discussionsupporting
confidence: 82%
“…Other perineuronal net components such as brevican are expressed at particularly high levels on the axon initial segment of mature hippocampal neurons58 and motor neurons in the superior colliculus59. ‘Axonal coats’ of aggrecan are also present in various human basal ganglia regions60, in the human lateral geniculate body61, and in the rat thalamus62, often independently of perineuronal nets. Interestingly, there is evidence that hyaluronan can control axonal outgrowth of optic tract and locus ceruleus neurons636465.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that ECM proteins are upregulated in synaptosomal preparations from APP/PS1 mice suggests an increase in perisynaptic ECM levels. Neuronal synthesis and synaptic release of ECM proteins might contribute to this upregulation [49,54]. The importance of perisynaptic ECM structures was demonstrated in hippocampal slice preparations where local treatment with ChABC enhanced spine motility without affecting PNNs [55].…”
Section: Discussionmentioning
confidence: 99%